MODERN TECHNOLOGIES AND METHODS IN LEARNING A FOREIGN LANGUAGE - Shodmonova, Azima Shodmonovna; Urinova, Mukhlisa Tokhirovna; Burkhanova, Ma’mura Gulyamovna (Innovative Development in Educational Activities, 2022)
The teacher of higher education should motivate students to use modern information technology training to study the discipline and develop professional competencies in foreign language teaching. The purpose of this research is to highlight the problem of finding the optimal didactic capabilities of modern information technologies used for improving the system of training specialists in the field of foreign languages teaching and to discuss the results of current studies in this direction.